2008
DOI: 10.1590/s0102-695x2008000300013
|View full text |Cite
|
Sign up to set email alerts
|

Estudo fitoquímico de goiaba (Psidium guajava L.) com potencial antioxidante para o desenvolvimento de formulação fitocosmética

Abstract: RESUMO:Considerando-se a qualidade dos fi toterápicos, é importante salientar que a preocupação com esta questão inclui rigoroso acompanhamento das diferentes etapas do desenvolvimento e produção destes produtos, desde a coleta do vegetal até a disponibilidade do produto fi nal. Neste trabalho, foram realizados o controle da qualidade, o potencial antioxidante como também ensaios biológicos in vitro do fruto da goiabeira (Psidium guajava L.), para o desenvolvimento de uma formulação fi tocosmética. Os resultad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
20

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 14 publications
3
12
0
20
Order By: Relevance
“…On the other hand, the essential oil showed no statistical difference compared with the control group showing low activity. Although the relationship between the data had Iha et al (2008) showed that the ethanolic extract of P. guajava had exhibited antioxidant activity, which, according to the authors, was owing the presence of flavonoids, a group of compounds also present in the extracts of the present study. Still, according to the authors, the antioxidant activity of P. cattleianum was reported for its fruits, due to the presence of phenolic compounds, especially flavonoids (Medina et al, 2011).…”
Section: Resultsmentioning
confidence: 47%
“…On the other hand, the essential oil showed no statistical difference compared with the control group showing low activity. Although the relationship between the data had Iha et al (2008) showed that the ethanolic extract of P. guajava had exhibited antioxidant activity, which, according to the authors, was owing the presence of flavonoids, a group of compounds also present in the extracts of the present study. Still, according to the authors, the antioxidant activity of P. cattleianum was reported for its fruits, due to the presence of phenolic compounds, especially flavonoids (Medina et al, 2011).…”
Section: Resultsmentioning
confidence: 47%
“…Possui ainda na sua constituição fitoquímicos como taninos, flavonoides, óleos essenciais, álcoois sesquiterpenoides e ácidos triterpenoides (Cheng, Shen e Wu, 2009;Iha et al, 2008). As sementes são ricas em fibras, principalmente celulose e lignina (Santos, 2011).…”
Section: Introductionunclassified
“…Avaliação in vitro da atividade fotoprotetora de extratos vegetais do cerrado de Mato Grosso Uma das tendências do mercado e da Ciência Cosmética é o desenvolvimento de produtos com maior número de componentes de origem natural, especialmente os de origem vegetal, explorando de forma racional a biodiversidade brasileira (Biavatti et al, 2007;Iha et al, 2008). Esta é vista com muito interesse pelo mercado internacional, principalmente se a matéria-prima apresenta estudos científicos comprovando a segurança e eficácia, além do comprometimento com o desenvolvimento sustentável (Franquilino, 2006).…”
Section: Introductionunclassified